Peran Orang Tua Dalam Menanamkan Nilai-nilai Keagamaan pada Anak - Octaviani, Fany; Muksin, Ucin; Marliana, Elly (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
The family is the first madrasa for their children and parents have the obligation to educate, nurture and guide children based on their religious teachings. The purpose of the research I wrote is that this research develops (1) the role of parents as mentors; (2) the example of parents in worship; (3) parental obedience in worship; (4) children's morality; (5) children's obedience in worship. The method used is descriptive qualitative method, which is research method that leads to actual problems. The results of the research are based on observations and interviews, namely (1) Lack of understanding of religious teachings; (2) less consistent; (3) monotonous guidance materials; (4) the media is still lacking; (4) the absence of rules and sanctions. After parents apply religious values to children, it shows a positive change, although not 100% perfect, but at least there is a change in behavior both in terms of mahdor worship and ghair mahdoh.